Internet of things: the use of raspberry pi, sensor devices and geo-fencing technology in fire detection monitoring system for a home / Norzatul Bazamah Azman Shah … [et al.] - Azman Shah, Norzatul Bazamah; Md Nor, Maryam Nabila; Zainuddin, Nurulhuda; Nasiron, Nur Asyira; Ramle, Rashidah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
Accidents caused by fire can result in serious injury and damage to personal property. Fire hazards are not always obvious in and around the home, so accidents involving fire are often unexpected and sudden. The main purpose of fire detection monitoring systems using Raspberry Pi is to provide an early warning for homeowners, to take immediate action to stop or eliminate fire effects as soon as possible. The system called Ifire provides a real time monitoring system, where they can receive push notification once the sensors are triggered. This system is a combination of technology using Internet of Things devices like temperature and humidity sensors (DHT11), infrared (IR) flame sensor, and mobile application. This system is an application that uses geo-fencing technology for homeowners, to find the nearest fire department to give a fast emergency response. Besides, it could help fire department staff to receive homeowner addresses and navigate directly to the location. The project was tested with functionality testing and network performance testing to make it work properly and successfully. The network performance testing shows the distance between Raspberry Pi and the access point will decrease when the distance increases. In addition, the response time testing result also shows the time during peak hour will decrease the performance. For future enhancements this Internet-based monitoring system will need security protection to prevent false fire information.